The Effects of Livelihood Assets and Livelihood Strategies on the Welfare Level of Community Forestry Farmers in Alam Lestari, West Lombok - Ainun Awallunisa Fatimah; Bramasto Nugroho; Leti Sundawati (Postgraduate, University of Mataram, 2025)
This study aims to analyze the relationship between livelihood strategies and the level of household welfare among farmers in The Alam Lestari Community Forestry. A total of 93 respondents were purposively selected and collected through questionnaires, interviews, and observations. Descriptive analysis was employed to depict the variation in livelihood assets and strategies, while the relationship between variables was examined using Spearman's Rank Correlation. The results reveal that livelihood strategies are primarily dominated by intensification and diversification, with migration not being a common strategy. Physical capital and social capital are the most significant assets supporting the diversity of strategy, while human capital and financial capital are relatively limited. Household welfare is moderate, with social indicators being the lowest component. Correlation tests show a positive and significant relationship between livelihood strategies and welfare (r = 0.407; p < 0.01), as well as a substantial relationship between livelihood assets and the variation in livelihood strategies. These findings emphasize that strengthening livelihood assets, particularly the physical and social aspects, plays a crucial role in fostering more adaptive livelihood strategies, which, in turn, contribute to improved household welfare among Community Forestry Farmers, and to the sustainability of community-based forest resource management